2021
DOI: 10.3390/ijerph182010712
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in the Center of Mediterranean: Comparison of the Two Calabrian Coasts and Distribution from Coastal Areas to the Open Sea

Abstract: Plastic is everywhere—increasing evidence suggests that plastic pollution is ubiquitous and persistent in ecosystems worldwide. Microplastic pollution in marine environments is particularly insidious, as small fragmentation can increase interaction with biota and food chain access. Of particular concern is the Mediterranean Sea, which has become a large area of accumulation of plastic debris, including microplastics, whose polymeric composition is still largely unknown. In this study, we analyzed the polymeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Microplastics have been found in seawaters in several recent studies, and when compared using the same unit of measurement (items·m –2 ) and mesh size of the tools (330 µm), our findings are consistent with those of others, such as those found in Tuscany’s coastal waters (0.069 ± 0.083 items·m –2 ; Baini et al 2018 ), in the Ligurian and Tyrrhenian Seas (0.25 ± 0.84 items·m –2 ; Caldwell et al 2020 ), and both in the Ionian and Tyrrhenian coasts (0.13 ± 0.19 items·m –2 ; Marrone et al 2021 ). As observed in the Mediterranean seawaters (Simon-Sánchez et al 2022 ), the results appear to reflect the high variability found in all three Italian subregions, with coastal mean values of 0.0616 items m –2 as compared to 0.0207 items m –2 in offshore waters.…”
Section: Discussionsupporting
confidence: 93%
“…Microplastics have been found in seawaters in several recent studies, and when compared using the same unit of measurement (items·m –2 ) and mesh size of the tools (330 µm), our findings are consistent with those of others, such as those found in Tuscany’s coastal waters (0.069 ± 0.083 items·m –2 ; Baini et al 2018 ), in the Ligurian and Tyrrhenian Seas (0.25 ± 0.84 items·m –2 ; Caldwell et al 2020 ), and both in the Ionian and Tyrrhenian coasts (0.13 ± 0.19 items·m –2 ; Marrone et al 2021 ). As observed in the Mediterranean seawaters (Simon-Sánchez et al 2022 ), the results appear to reflect the high variability found in all three Italian subregions, with coastal mean values of 0.0616 items m –2 as compared to 0.0207 items m –2 in offshore waters.…”
Section: Discussionsupporting
confidence: 93%
“…In nature, plastic waste is degraded and fragmented into smaller micro-and nanoparticles with sizes less than 5 mm [4]. Owing to their small size, micro-plastic can be easily dispersed and become waterborne [5][6][7][8], soil-borne [9,10], airborne pollutants [11]. From the domestic and industrial environment microplastic could enter the aquatic and terrestrial ecosystem through incomplete removal in wastewater treat-ment plants and…”
Section: Introductionmentioning
confidence: 99%
“…In both seasons the predominant colors were transparent (37.4% in summer and 62.2% in winter) and white (25.8% in summer and 35.6% in winter). The predominance of light colors was also recorded by Van der Hal et al (2017) along the Israeli Mediterranean coast in both summer and winter and by Marrone et al (2021) in the central part of the Mediterranean Sea. In contrary to the microplastic color distribution in Yarkon samples, in the Sado samples the green particles (32.54%) were the most abundant in the summer; and the blue particles (29.23%) were the most abundant in the winter.…”
Section: Discussionmentioning
confidence: 69%
“…The predominance of fragments in both seasons in Yarkon, agrees with the most frequently found typologies along the Mediterranean coast of Israel (93.6-97.7%;van der Hal et al, 2017), Mediterranean basin (87.7%; Cózar et al, 2015) and in open and coastal waters of the eastern Mediterranean Sea (including the Ionian and Levantine seas; 50-60%; Adamopoulou et al, 2021). The high percentage of films documented in the winter (37.78%), can be explained by the faster degradation of plastic bags and packaging, which is considered their main source (Marrone et al, 2021). The same was observed for Sado, where fragments predominated during summer (63.49%) and winter (76.34%), which is in agreement with samples from the North East Atlantic (63%) and from Arrábida and Setúbal (Rodrigues et al, 2022).…”
Section: Discussionmentioning
confidence: 99%